On the Rise of Social Media Influencer Marketing: A Systematic Literature Review and Future Research Agenda - Bansah, Pearl Fafa; Gaffar, Vanessa; Disman, Disman; Yuliawati, Ayu Krishna (Universitas Pendidikan Indonesia, 2024)
The study aimed to explore the definitions and principles of social media influencers (SMIs) and investigate their role as a marketing strategy. A systematic literature review was conducted using databases such as EBSCOhost, ScienceDirect, and Emerald, resulting in 89 peer-reviewed articles from 2007 to 2023. The findings revealed various definitions of SMIs, highlighting their role as marketing communication tools to influence consumer purchase intention. SMIs were described as individuals with a large fan base, attracting a significant following and becoming advisors to their followers. The study also identified a growing trend of businesses using influencers in their communication strategies. Additionally, the elements of influencer brand-fit, engagement, attractiveness, expertise, and perceived credibility were found to impact consumer purchase intention. Overall, the research provides valuable insights into the field of influencer marketing and its effects.